Web-Based Letter Processing and System Design (Case Study of the Bungo District Communication and Information Service) - Taufik hidayat; Sepriano; Harwindra Kurnia Adi; M. Taufik; Yonifan Mufatgiin (Indonesian Journal of Contemporary Multidisciplinary Research, 2022)
The use of information technology in the government industry is very important in the digital era as it is today because the use of information and communication technology in government processes can increase efficiency, effectiveness, transparency and accountability in the administration of public service government. The Bungo Regency Communications and Information and Coding Service, which is one of the government agencies in information and communication technology, has several obstacles, namely there are still many unmet needs, such as websites. An information system in the form of a website and web-based mail processing is needed to improve the quality and efficiency of the mail processing process